Determining Functional Safety Indices of CWR Track Subject to Action of Thermal Compression Forces - O. A. Suslov (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
Two main railway track design versions may be observed on the JSC RZD network. They are jointed track and con-tinuous welded rail track of temperature strained type. For the time being JSC RZD is well on the way from predictive track maintenance pattern to the pattern implying actual track condition analysis based planning of the quantities of maintenance work and respective expenditures. The key feature of such an approach lies in the necessity to determine indices characterizing tack design version as a system ensuring safety of railway traffic operations. In the present paper there is proposed failure probability assessment algorithm based on the thermal track buckling emergence criterion. It has been confirmed that the existing standards ensure the required operational safety level of a track design version in the context of the indicated criterion.